Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(12:y=\frac{3}{4}+\frac{4}{5}\)
\(12:y=\frac{15}{20}+\frac{16}{20}\)
\(12:y=\frac{31}{20}\)
\(y=12:\frac{31}{20}\)
\(y=12x\frac{20}{31}\)
\(y=\frac{240}{31}\)
\(\frac{4}{5}xY=1\)
\(y=1:\frac{4}{5}\)
\(y=1x\frac{5}{4}\)
\(y=\frac{5}{4}\)
\(\frac{37}{63}-y=\frac{1}{7}\)
\(y=\frac{37}{63}-\frac{1}{7}\)
\(y=\frac{37}{63}-\frac{9}{63}\)
\(y=\frac{28}{63}\)
\(y=\frac{4}{9}\)
\(y:\frac{3}{7}=\frac{3}{42}+\frac{5}{7}\)
\(y:\frac{3}{7}=\frac{3}{42}+\frac{30}{42}\)
\(y:\frac{3}{7}=\frac{33}{42}\)
\(y:\frac{3}{7}=\frac{11}{14}\)
\(y=\frac{11}{14}x\frac{3}{7}\)
\(y=\frac{33}{98}\)
\(12:y=\frac{3}{4}+\frac{4}{5}\) \(\frac{37}{63}-y=\frac{1}{7}\)
\(12:y=\frac{31}{20}\) \(y=\frac{37}{63}-\frac{1}{7}\)
\(y=12:\frac{31}{20}\) \(y=\frac{4}{9}\)
\(y=\frac{240}{31}\)
\(\frac{4}{5}\cdot y=1\) \(y:\frac{3}{7}=\frac{3}{42}+\frac{5}{7}\)
\(y=1:\frac{4}{5}\) \(y:\frac{3}{7}=\frac{11}{14}\)
\(y=\frac{5}{4}\) \(y=\frac{11}{14}.\frac{3}{7}\)
\(y=\frac{33}{98}\)
a,
\(y:\dfrac{2}{5}=12\)
\(y=12\times\dfrac{2}{5}\)
\(y=\dfrac{24}{5}=4,8\)
b,
\(\dfrac{11}{10}+\dfrac{4}{5}\times\dfrac{3}{4}=\dfrac{11}{10}+\dfrac{12}{20}=\dfrac{22}{20}+\dfrac{12}{20}=\dfrac{34}{20}=\dfrac{17}{10}\)
\(y\times\frac{3}{5}+y\times\frac{2}{7}=\frac{31}{70}\)
\(\Leftrightarrow y\times\left(\frac{3}{5}+\frac{2}{7}\right)=\frac{31}{70}\)
\(\Leftrightarrow y\times\frac{31}{35}=\frac{31}{70}\)
\(\Leftrightarrow y=\frac{1}{2}\)
\(\frac{2}{3}x\frac{4}{y}=\frac{4}{45}:\frac{1}{5}\)\(=\frac{4}{15}\)
\(\frac{4}{y}=\frac{4}{15}:\frac{2}{3}\)\(=\frac{2}{5}\)
y=4:\(\frac{2}{5}\) y=10
\(\frac{3}{4}x\frac{y}{5}=\frac{15}{4}\)
\(\frac{y}{5}=\frac{15}{4}:\frac{3}{4}=5\)
y=5x5=25
bài 1 :
\(\frac{5}{12}\) + \(\frac{1}{3}\) = \(\frac{5}{12}\) + \(\frac{4}{12}\) = \(\frac{5+4}{12}\) = \(\frac{9}{12}\) = \(\frac{3}{4}\)
1 - \(\frac{3}{4}\) = \(\frac{4}{4}\) - \(\frac{3}{4}\) = \(\frac{4-3}{4}\) = \(\frac{1}{4}\)
2 x \(\frac{3}{11}\) = \(\frac{2x3}{11}\) = \(\frac{6}{11}\)
\(\frac{8}{7}\): 4 = \(\frac{8}{7x4}\) = \(\frac{8}{28}\) = \(\frac{2}{7}\)
bài 2 :
\(\frac{2}{5}\) : y = \(\frac{1}{3}\)
y = \(\frac{2}{5}\) : \(\frac{1}{3}\)
y = \(\frac{6}{5}\)
y : \(\frac{7}{11}\) = 22
y = 22 x \(\frac{7}{11}\)
y = 14
ai thấy đúng tk nha
3/5*y-4/5:3+1/12=3/2+1/5
3/5*y-4/5:3+1/12=17/10
3/5*y-4/15=17/10-1/12
3/5*y-4/15=97/60
3/5*y=97/60+4/15
3/5*y=113/60
y=113/60:3/5
y=113/36 ( cho mik nha)
- x + \(\frac{9}{7}\)= \(\frac{4}{5}\)
=> x = \(\frac{4}{5}\)- \(\frac{9}{7}\)
=> x = \(\frac{-17}{35}\)
- x - \(\frac{5}{2}\)= \(\frac{12}{7}\)
=> x = \(\frac{12}{7}+\frac{5}{2}\)
=> x = \(\frac{59}{14}\)
- \(\frac{29}{3}\)- x = \(\frac{5}{6}\)
=> \(\frac{29}{3}\)- \(\frac{5}{6}\)= x
=> \(\frac{53}{6}\)= x
=> x = \(\frac{53}{6}\)
+)\(x+\frac{9}{7}=\frac{4}{5}\)
<=>\(x=-\frac{17}{35}\)
+)\(x=\frac{59}{14}\)
+)\(x=\frac{53}{6}\)
y-3/4= 5/12:10/3 y-3/4 =5/12*3/10 y -3/4=1/8 y=1/8+3/4 y=7/8